2021
DOI: 10.1111/jan.14738
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of mindfulness‐based interventions for patients with coronary heart disease

Abstract: Aims To assess the effects of mindfulness‐based interventions for patients with coronary heart disease. Design A systematic review with meta‐analysis. Data sources Eight mainstream databases, including Ovid MEDLINE, Embase, Ovid Emcare, PsycInfo, CINAHL complete, Web of Science, CENTRAL and PubMed, were searched from January 1979–March 2020. Review methods Randomized controlled trials that evaluated mindfulness‐based interventions on psychological outcomes, cardiovascular risk factors and quality of life in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…The intervention was a six-week group intervention based on the principles of Mindfulness-Based Stress Reduction [ 23 , 24 , 42 ]. Kabat Zinn’s research has had a great impact on the development of mindfulness programs applied to different settings, with solid evidence regarding their effectiveness [ 43 , 44 ]. Our intervention was based on his teachings and combines elements of MBCT [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intervention was a six-week group intervention based on the principles of Mindfulness-Based Stress Reduction [ 23 , 24 , 42 ]. Kabat Zinn’s research has had a great impact on the development of mindfulness programs applied to different settings, with solid evidence regarding their effectiveness [ 43 , 44 ]. Our intervention was based on his teachings and combines elements of MBCT [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Implementing relevant measures to decrease risk factors of CHD is the most important strategy in secondary prevention of the condition, which is often referred to as "ABCDE" strategy (Hu et al, 2019;Smith et al, 2011). Lu et al, 2020;Mellwig et al, 2017;Pedersen et al, 2019;Pogosova et al, 2019;Zou et al, 2021). However, in our study, six primary outcomes and three secondary outcomes were verified according to the "ABCDE" strategy.…”
Section: Secondary Prevention Of Chdmentioning
confidence: 61%
“…In previous studies, researchers only addressed one or two health outcomes in a single study, such as medication compliance, exercise, weight loss, LDL‐C control, health education, or psychology (Jiang et al, 2019; Lu et al, 2020; Mellwig et al, 2017; Pedersen et al, 2019; Pogosova et al, 2019; Zou et al, 2021). However, in our study, six primary outcomes and three secondary outcomes were verified according to the “ABCDE” strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary heart disease (CHD), an ischemic heart disease, is caused by coronary atherosclerosis. Patients have different degrees of lumen occlusion and stenosis, resulting in myocardial ischemia, hypoxia, and necrosis, with the main clinical manifestations as chest pain (paroxysmal colic or crush pain) and chest distress [ 1 ]. According to China's fifth health service survey in 2013, the number of CHD patients over 15 years old in China exceeded 10 million [ 2 ], and China's Health and Family Planning Statistical Yearbook (2016) confirmed that the number was still on the rise.…”
Section: Introductionmentioning
confidence: 99%